(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Biodiversity is the difference between life forms that highlights the abundance and significance of living organisms in the ecosystem. Physiochemical parameters of water and soil have extreme significance in the distribution of aquatic life and also in the breeding of aquatic organisms. Studies on the length-weight relationship are very important for fishery biology and stock assessment of fisheries resources. This research was carried out to elaborate on fish diversity, physicochemical parameters of water and soil, length-weight relationships (LWR) and condition factor (K) of fishes of the Urbashi dam in Karak, Khyber Pakhtunkawa, Pakistan. Fish samples were collected with the help of local fisherman through nets, drag nets, gill nets, and cast nets from October 2020 to July 2021. The specimens were preserved in a 10% formalin solution. The length and weight of fish samples were determined with the help of a measuring tape and a digital balance. The physiochemical parameters like conductivity, PH, temperature, color, taste, TS, and TDS of water and soil were examined by collecting (n=3) samples from different sites of the Urbashi dam, i.e., the start, mid, and end